1983
DOI: 10.3109/00016348309155762
|View full text |Cite
|
Sign up to set email alerts
|

Positional Factors of the Uterus Play a Contributing Part in Iud Failure

Abstract: This study is based on a uniform material of 3 500 copper IUD insertions at the Family Planning Unit of Turku Health Center, including 72 cases resulting in pregnancy. Among the pregnant subjects there were significantly more women with a retroverted flexed or mid-positioned uterus than in the control material. Repeat IUD pregnancies were rather common. These observations should be taken into account in practice, especially regarding great care with the insertion technique and a close follow-up of these women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…9 Young maternal age, heavy menstruation, dysmenorrhoea, uterine position, and the service provider's experience with regard to insertion were reported to be associated with expulsion or removal for displacement. [10][11][12][13][14][15] One hypothesis for IUD expulsion or displacement is dimensional incompatibility between the uterine cavity and the IUD. Castro found that the expulsion rate within 1 and 2 years of MLCu375 was more than four times higher for women with an endometrial cavity length of ≥45 mm, compared with those with a cavity length of <45 mm (P < 0.01) 16 ; however, two prospective studies failed to find any association between endometrial cavity length and the expulsion rate of IUDs.…”
Section: Introductionmentioning
confidence: 99%
“…9 Young maternal age, heavy menstruation, dysmenorrhoea, uterine position, and the service provider's experience with regard to insertion were reported to be associated with expulsion or removal for displacement. [10][11][12][13][14][15] One hypothesis for IUD expulsion or displacement is dimensional incompatibility between the uterine cavity and the IUD. Castro found that the expulsion rate within 1 and 2 years of MLCu375 was more than four times higher for women with an endometrial cavity length of ≥45 mm, compared with those with a cavity length of <45 mm (P < 0.01) 16 ; however, two prospective studies failed to find any association between endometrial cavity length and the expulsion rate of IUDs.…”
Section: Introductionmentioning
confidence: 99%